2022
DOI: 10.3389/fenvs.2022.975282
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of land transfer marketization on green total factor productivity from the perspective of resource allocation: Evidence from China

Abstract: Exploring the determinants of green total factor productivity (green TFP) is of great importance to economic performance and ecological sustainability. Based on the data of 30 provincial units in China from 2004 to 2016, this study first analyzes the mechanism of land transfer marketization (LTM) affecting green TFP through resource allocation, then the regional resource allocation level is measured using the indicator of factor market distortion, and regional green TFP is estimated by the slack-based measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…There have been many classic discussions on government and economic development [35][36][37][38]. Some studies have shown the promotional effect of governmental regulations on economic development [39][40][41][42][43]. However, some studies have proved a negative relationship between them [44][45][46].…”
Section: The Mechanism By Which the Degree Of Governmental Regulation...mentioning
confidence: 99%
“…There have been many classic discussions on government and economic development [35][36][37][38]. Some studies have shown the promotional effect of governmental regulations on economic development [39][40][41][42][43]. However, some studies have proved a negative relationship between them [44][45][46].…”
Section: The Mechanism By Which the Degree Of Governmental Regulation...mentioning
confidence: 99%